Unterwegs zur Sprache - Heidegger, Martin 1889-1976 (Pfullingen Neske, 1960)
Few philosophers before him have dealt with poetry in a comparably intensive way as Heidegger did in order to uncover a fundamental feature of his thinking. With the exception of the conversation written down in 1953/54, the texts are lectures held by Heidegger between 1950 and 1959. In the first two texts, Heidegger leads his hermeneutical conversation with the poetry of Georg Trakl, while the fourth and fifth text deal with Stefan Georges´s late poetry. In these conversations the philosopher thinkingly pursues the essence of language from the insight into the adjacency of poetry and thinking. Heidegger describes this adjacency as being kept apart by a "delicate but bright difference." The question of the respective essence of thinking and poetry thus simultaneously constitutes the quest for the essence of philosophy.
Keywords: 20th Century (1901-2000); Philosophy; Poetry; Germany